Analisis Minat Baca Siswa pada Cerita Pendek Menjaga Kelestarian Hutan Kelas V Sekolah Dasar Negeri Sidomulyo - Firman Pratomo Aji (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aimed to analyze the reading interest of fifth-grade students at SD Negeri Sidomulyo toward the short story Preserving Forest Sustainability. The research employed a qualitative approach with a descriptive research design. The participants consisted of the fifth-grade teacher and students of SD Negeri Sidomulyo. Data were collected through interviews, observations, and documentation. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the students' reading interest in the short story Preserving Forest Sustainability was categorized as good. Students were interested in reading the story because it used simple and easy-to-understand language and contained engaging content. Furthermore, the theme of forest conservation enhanced students' understanding of and concern for environmental issues. Teachers also played an important role in fostering students' reading interest by providing reading materials that matched their interests. However, excessive use of gadgets at home remained one of the obstacles to developing students' reading habits. Therefore, environmental-themed short stories can serve as an effective alternative reading material to improve reading interest while instilling environmental awareness among elementary school students.